Peran Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran PAI di MI Tahfidz Hdwr Bantul - Muhammad Bahrul Bahar; Dhian Kurniawati; Diah Ayu Tazkia Ramadhani; Hasan Safrudin; Inayatun Nupus (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
The role of the Principal in improving the educational motto and learning process of PAI (Islamic Religious Education) is very significant. The principal's role as a leader and motivator can increase the awareness and commitment of teachers, students and the community towards the motto of education that is oriented towards religious values. Therefore, the Principal must have a clear vision and effective strategy to improve the educational motto and learning process of PAI. In improving the motto of education, school principals can make various efforts, such as holding activities oriented to religious values, developing relevant and effective curricula, and increasing teacher and student participation in the learning process. Apart from that, school principals must also improve teachers' abilities in teaching PAI, as well as improve the facilities and infrastructure available to support the learning process. In improving the PAI learning process, the Principal can make various efforts, such as holding activities oriented to religious values, developing a relevant and effective curriculum, and increasing teacher and student participation in the learning process. Apart from that, school principals must also improve teachers' abilities in teaching PAI, as well as improve the facilities and infrastructure available to support the learning process. In synthesis, the role of the Principal in improving the educational motto and learning process of PAI is very significant. Therefore, the Principal must have a clear vision and effective strategy to improve the educational motto and learning process of PAI.